Topical estrogens and non-hormonal preparations for postmenopausal vulvovaginal atrophy: An EMAS clinical guide. (June 2021) - Hirschberg, Angelica Lindén; Bitzer, Johannes; Cano, Antonio; Ceausu, Iuliana; Chedraui, Peter; Durmusoglu, Fatih; Erkkola, Risto; Goulis, Dimitrios G.; Kiesel, Ludwig; Lopes, Patrice; Pines, Amos; van Trotsenburg, Mick; et al.
Highlights: Vulvovaginal atrophy is a chronic condition caused by estrogen deficiency. It affects around 50% of postmenopausal women, reducing their general and sexual quality of life as well as the quality of their personal relationships. Both topical estrogens and non-hormonal lubricants and moisturizers can be used to treat vulvovaginal atrophy. Non-hormonal preparations should be the first-line treatment for vulvovaginal atrophy in women taking adjuvant endocrine therapies for cancers considered to be hormone dependent. Abstract: Introduction: Vulvovaginal atrophy (VVA) is a chronic condition caused by estrogen deficiency. It affects around 50% of postmenopausal women, reducing their general and sexual quality of life as well as the quality of their personal relationships. Aim: The aim of this clinical guide is to set out an individualized approach to the management of VVA with topical estrogens and non-hormonal preparations. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: An individualized approach is required for the management of VVA. Topical low-dose estrogens are effective and also alleviate urinary incontinence and prevent recurrent urinary tract infections. Women should not be denied long-term use of topical estrogens as long as they feel that this treatment is of benefit to them, because the safety data are reassuring. Non-hormonal preparations (lubricants and moisturizers) should be the first-line treatment for VVA in women taking adjuvant endocrine therapies for cancers considered to be hormone-dependent. They can be used over the long term.